2012
DOI: 10.1002/jcop.20518
|View full text |Cite
|
Sign up to set email alerts
|

A Validation Study of the Italian Version of the Resilience Scale for Adolescents (Read)

Abstract: The validity of the Italian version of the 28‐items Resilience Scale for Adolescents (READ) was examined. A sample of 472 senior high school students between 18 and 20 years of age were used for this purpose. Reliability and validity were investigated by means of Cronbach's alpha, exploratory factor analysis, and confirmatory factor analysis. The results supported the construct validity of the five factors of the scale, which yielded acceptable psychometric properties. The findings conclude that the READ is a … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
30
0
1

Year Published

2013
2013
2024
2024

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 26 publications
(36 citation statements)
references
References 13 publications
3
30
0
1
Order By: Relevance
“…The five factors showed significant and moderateto-high factor correlations, indicating that the resilience dimensions should be regarded as factors measuring different, but related aspects of resilience; however, the factors can still be regarded as substantially unique. Although serious misspecifications of the original model were found, especially related to the factor 'structured style' which only included two items, the CFA gave support for the 20-item five-factor structure in the two samples tested, which generally agree with the empirical development and original dimensionality of the READ as published in previous studies (10,22,23). Meanwhile, the post hoc modelling approach and development of a modified factor structure requires the need for more testing regarding the validity and stability of the instrument in other adolescent samples (45).…”
Section: Factor Structuresupporting
confidence: 83%
See 3 more Smart Citations
“…The five factors showed significant and moderateto-high factor correlations, indicating that the resilience dimensions should be regarded as factors measuring different, but related aspects of resilience; however, the factors can still be regarded as substantially unique. Although serious misspecifications of the original model were found, especially related to the factor 'structured style' which only included two items, the CFA gave support for the 20-item five-factor structure in the two samples tested, which generally agree with the empirical development and original dimensionality of the READ as published in previous studies (10,22,23). Meanwhile, the post hoc modelling approach and development of a modified factor structure requires the need for more testing regarding the validity and stability of the instrument in other adolescent samples (45).…”
Section: Factor Structuresupporting
confidence: 83%
“…The READ is a modified version of the Resilience Scale for Adults (RSA) and has provided support for a five‐factor structure: (i) Personal competence ; (ii) Structured style ; (iii) Social competence ; (iv) Social Resources and (v) Family Cohesion . Recent validation studies of the READ have demonstrated inconsistencies of the dimensionality with a number of misfit items in samples with Norwegian and Italian high school students 18–20 years . Nevertheless, the READ has shown satisfying reliability with Cronbach's alphas ranging from α = 0.69 (structured style) to α = 0.89 (family cohesion) .…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations
“…It consists of five factors; (1) Personal Competence; (2) Social Competence; (3) Structured Style; (4) Family Cohesion; and (5) Social Resources. The Italian validated translation of the original version was used (Stratta et al, 2012b).…”
Section: Methodsmentioning
confidence: 99%